Science teaching and playfulness: Potentialities of the application "Desrotulando" as an educational resource - Correia , Mateus de Lima; Sousa , Carlos Erick Brito de (Seven Editora, 2023)
In this work, of qualitative nature and documentary nature, the possibilities of an application, which does not have didactic purposes, as an educational resource for playful approaches in Science Teaching on topics related to food and health are investigated. Data collection took place through the capture of screens with a smartphone device, seeking elements in all areas of the application, taking into account its other tools. The process of data analysis occurred through proposals of documentary research, considering the processes of exploratory, selective, analytical and interpretative reading. With regard to interpretation, this occurred through correlations with the theoretical references of the areas of Biochemistry, Playfulness and Science Teaching. From the analyses, it is possible to conclude that the application, when thought of as an educational resource, presents potentiality for the development of playful approaches in the teaching of Sciences, fostering an active posture in the production of knowledge. In addition, the content has accessible and easily understood language, without losing the meaning of the concepts that are addressed about nutrients and health. However, the application only does not guarantee that the student reflects on the deeper aspects of these themes, being fundamental the role of the educator in the process of deepening, problematizing and contextualizing on the topics addressed. DOI:https://doi.org/10.56238/uniknowindevolp-001